ALAT PEMANTAU KONDISI PASIEN MENGGUNAKAN ARDUINO UNO DENGAN TAMPILAN GRAFIK TERHUBUNG THINGSPEAK - Marwanto, Marwanto; Suharjanto, Suharjanto; Jeniyansah, Feby Rantau (Teknika, 2024)
The development of science and technology is very influential in all fields, including the health and medical fields. To increase the value of medical personnel services, monitoring patient conditions in real-time is necessary. Medical personnel need information on the patient's condition to take preventive and effective action. The information required by medical personnel is vital signs of the patient's condition in the form of heart rate and body temperature. The patient's heart rate condition can be read with a pulse sensor, while body temperature can be read with the DS18B20 temperature sensor. The results of the heart rate and body temperature sensor readings are displayed on the Liquid Crystal Display(LCD) screen with the help of the Inter-Integrated Circuits (I2C) module when communicating with the Arduino Uno. So that medical personnel can monitor the condition of the patient's heart rate and body temperature remotely without using cables, an intelligent cellphone with the Thingspeak platform application is used. Smartphones with the Thingspeak application can communicate with heart rate and body temperature sensors with the help of the ESP8266-01 module. From the research that has been carried out, it was found that the average error in temperature readings was 1.4% and heart rate was 3.6%. This patient condition monitoring tool can be implemented in hospitals to monitor the patient's condition through heart rate and body temperature. From the research that has been carried out, it was found that the average error in temperature readings was 1.4% and heart rate was 3.6%. This patient condition monitoring tool can be implemented in hospitals to monitor the patient's condition through heart rate and body temperature.